Canine atopic dermatitis: breed risk in Australia and evidence for a susceptible clade. Issue 3 (June 2016) - Mazrier, Hamutal; Vogelnest, Linda J.; Thomson, Peter C.; Taylor, Rosanne M.; Williamson, Peter
Abstract : Background: Genetic studies on canine atopic dermatitis (CAD) indicate that large populations from one geographical location are preferred for the identification of relevant susceptibility genes. Australian dogs are relatively isolated; studies on CAD in this population are limited. Hypothesis/Objectives: To identify breeds at risk in the Australian dog population and to compare with worldwide breed predisposition. Animals: Case records ( n  =   23, 000) from University Veterinary Teaching Hospital (UVTH) dogs, including 722 with CAD. Methods: The breed proportion of CAD and odds risk (OR) were calculated. A systematic review of 13 previous studies (1971–2010) was performed and compared to the study results by implementing an atopic dermatitis (AD)‐to‐reference population ratio (ADRPR). Results: Eleven dog breeds with significant increased OR (≥1.0) were identified; all with breed CAD cases proportionally higher than their base hospital population. Gender risk in males from the pug dog breed ( P  =   0.007) was detected and the bichon frise breed had a similar trend ( P  =   0.05). Sixteen predisposed dog breeds were identified by systematic review. All breeds with significant increased OR in UVTH had ADRPR > 1.4; five (boxer, bulldog, Labrador retriever, pug, West Highland white terrier) were recognized as predisposed worldwide. One clade of breeds with common ancestry was highly represented in CAD cases worldwide and in Australia (81% of the significant OR cases). Conclusion and clinical importance: The use of a large population from one geographical location and ADRPR provided an objective comparison between worldwide AD studies; it identified one common clade of susceptible breeds. Breed genetics and related clinical presentation may help CAD diagnosis and treatment. Abstract : Background ‐ Genetic studies on canine atopic dermatitis (CAD) indicate that large populations from one geographical location are preferred for the identification of relevant susceptibility genes. Australian dogs are relatively isolated; studies on CAD in this population are limited.Hypothesis/Objectives ‐ To identify breeds at risk in the Australian dog population and to compare with worldwide breed predisposition.Conclusion and clinical importance ‐ The use of a large population from one geographical location and ADRPR provided an objective comparison between worldwide AD studies; it identified one common clade of susceptible breeds. Breed genetics and related clinical presentation may help CAD diagnosis and treatment.